Pelvic occupation: the challenges of treating a symptomatic tarlov cyst. (4th May 2019) - Khan, Amad; Wilson, Holly Y.; Boeris, Davide; Nelson, Richard
Abstract: Tarlov (perineural) cysts are meningeal dilations of the posterior spinal nerve root sheath located in between the peri- and endoneurium. We present a patient with a symptomatic sacral Tarlov cyst and the technical challenges faced by surgically treating the lesion by disconnection of the cyst from the subarachnoid space.